2020
DOI: 10.1038/s41598-020-62178-6
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behaviour of the South American sea lion (Otaria byronia) in two disparate ecosystems assessed through blubber fatty acid analysis

Abstract: Fatty acids have been widely used as trophic biomarkers in marine mammals. However, for the South American sea lion, the most abundant otariid in the eastern South Pacific, there is no information about blubber fatty acids and their link to diet. Here, we compare fatty acid profiles of sea lions from two distinct oceanographic regions in northern and southern chile. their fatty acids vary greatly between regions, suggesting dietary differences at a spatial scale. The fatty acid C22:6ω3 was more abundant in sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 84 publications
0
8
0
1
Order By: Relevance
“…Outer layer FAs, for example, maintain their composition during lactation in Weddell seals (Wheatley et al 2007 ), and northern elephant seals (Fowler et al 2014 ). However, although the proportion of FAs may differ between layers, the overall FA pattern is similar (Hooker et al 2001 ); thus, the outer layer is thought to be an indicator of longer-term diet (Moller et al 2003 ; Budge et al 2006 ; Guerrero et al 2020 ) compared to the inner layer that reflects from hours to months (Kirsch et al 2000 ; Budge et al 2004 , 2006 ). Here, we used only the outer layer for FA analysis since it can be obtained remotely, hence, requires comparatively less effort and lower economic costs than the collection of whole blubber samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Outer layer FAs, for example, maintain their composition during lactation in Weddell seals (Wheatley et al 2007 ), and northern elephant seals (Fowler et al 2014 ). However, although the proportion of FAs may differ between layers, the overall FA pattern is similar (Hooker et al 2001 ); thus, the outer layer is thought to be an indicator of longer-term diet (Moller et al 2003 ; Budge et al 2006 ; Guerrero et al 2020 ) compared to the inner layer that reflects from hours to months (Kirsch et al 2000 ; Budge et al 2004 , 2006 ). Here, we used only the outer layer for FA analysis since it can be obtained remotely, hence, requires comparatively less effort and lower economic costs than the collection of whole blubber samples.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical methods, such as fatty acid (FA) and stable isotope (SI) analyses, can reconstruct diets by overcoming the caveats of the traditional techniques. These two biochemical methods are based on the principle that an animal’s diet is reflected in the patterns of FAs and SIs of their tissues (Hooker et al 2001 ; Guerrero et al 2020 ). Many FAs, particularly polyunsaturated FAs, can only be synthesized at low trophic levels and are transferred to higher trophic levels with minimal modification (Iverson 1993 ) and thus, can be used to distinguish dietary preferences (Dalsgaard et al 2003 ; Guerrero et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transverse variation in FAs across the blubber has been attributed to the different roles that the outer and inner blubber layers play [55][56][57] . The FAs of the inner blubber layer have an active turnover rate as they are more directly influenced by the consumer's diet 56,58,59 while the FAs in the outer blubber play an active role in thermoregulation 55 , they are more stable and less affected by short-term dietary changes 55,60,61 . For example, Struntz et al 61 observed that the outer layer of bottlenose dolphins, Tursiops truncatus, remained unchanged after a period of undernourishment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that there are geographic differences in blubber FA composition of various marine mammal species, for example, bearded seals [Erignathus barbatus (Erxleben, 1777)], beluga whales [Delphinapterus leucas (Pallas, 1776)], ringed seals [Pusa hispida (Schreber, 1775)], walruses [Odobenus rosmarus (Linnaeus, 1758)], harbor seals (Phoca vitulina Linnaeus, 1758) and sea lions [Otaria byronia (de Blainville, 1820)], particularly in the MUFA and PUFA compositions and distributions within their blubbers (Thiemann et al 2008;Guerrero et al 2020). Most studies attributed the geographic differences in blubber FA composition to the diet, but a strong impact from FA metabolism was also found among common minke whales (Balaenoptera acutorostrata Lacépède, 1804) from different regions (Meier et al 2016).…”
Section: Introductionmentioning
confidence: 99%